Role of cytokines, IL1-β and IL-10, in the development of endocrine ophthalmopathy in Graves' disease - Yu. V. Buldygina; H. A. Zamotaieva; G. M. Terekhova; N. M. Stepura; V. M. Klochkova; T. V. Fed'ko (Ukrainian Society of Ophthalmologists, 2021)
Background: Endocrine ophthalmopathy (EO) is a disease which is characterized by progressive autoimmune inflammation of extraocular muscles and retrobulbar adipose tissue, and is accompanied by infiltration, edema and proliferation of retrobulbar adipose tissue, muscles and connective tissue, leading to worsened quality of life, limited capacity for work and even ocular atrophy. It has been demonstrated that cytokines are involved in the development of autoimmune ophthalmopathy in Graves' disease (GD). Thus, the secretion of IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, and TNFα were increased several dozenfold in active ophthalmopathy, but the specificity of cytokines in EO is still a subject of discussion among researchers. Purpose: To assess the levels of proinflammtory cytokines (IL-1β) and anti-inflammatory cytokines (IL-10) in Graves' disease complicated by endocrine ophthalmopathy. Material and Methods: Forty-three patients with Graves' disease (33 women and 10 men; age, 18 to 71 years) underwent an examination. They were divided into two groups based on the presence or absence of EO: GD plus EO (24 patients) and GD only (19 patients). Disease duration was 2.2±0.4 years for patients with GD plus EO versus 3.98±0.74 years for patients with GD only (р<0.05). All patients were treated with antithyroid drugs (mercazolil and thyrozol) and were classified as having compensated thyroid disease at the time of the study. All patients with GD plus AO had a CAS score exceeding 3 (the active stage of EO). Patients underwent an examination including ultrasonic assessment of thyroid gland volume, hormonal examination (serum TSH, free T4 (fT4), and free T3 (fT3)), assessment of serum antithyroid antibodies (anti-thyroid peroxidase antibodies and TSHR-Ab) and serum IL-1β and IL-10 levels. Results: Serum IL-1β levels were significantly increased in patients with Graves' disease compared to healthy controls. Serum IL-1β levels for patients with GD plus EO were significantly higher than for patients with GD only (45.48 ± 16.19 pg/ml versus 10.44±5.17 pg/ml; р < 0.05), which may indicate the specificity of this cytokine as a marker of inflammatory autoimmune activity in the orbit. Serum IL-10 levels were significantly increased in all patients with Graves' disease, with no significant difference in this characteristic between patients with GD plus EO and patients with GD only (23.76±7.72 pg/ml versus 22.21±2.82 pg/ml; р > 0.05).